2022
DOI: 10.3390/jcm11082107
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Early Postoperative Cardiac Rehabilitation in Patients with Acute Type A Aortic Dissection

Abstract: Introduction: Surgically treated acute type A aortic dissection (ATAAD) patients are often restricted from physical exercise due to a lack of knowledge about safe blood pressure (BP) ranges. The aim of this study was to describe the evolution of early postoperative cardiac rehabilitation (CR) for patients with ATAAD. Methods: This is a retrospective study of 73 patients with ATAAD who were referred to the CR department after surgery. An incremental symptom-limited exercise stress test (ExT) on a cyclo-ergomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…in-bed cycling); however, the systolic blood pressure remained below 160 mmHg, and no serious adverse events related to exercise were observed. These findings are consistent with those reported by Zhou et al 6 Regular exercise reduces the resting blood pressure of patients. 8 Exercise results in modification of blood flow, luminal shear stress, arterial pressure, and tangential wall stress, all of which are factors that can induce changes in arterial function, diameter, and wall thickness.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…in-bed cycling); however, the systolic blood pressure remained below 160 mmHg, and no serious adverse events related to exercise were observed. These findings are consistent with those reported by Zhou et al 6 Regular exercise reduces the resting blood pressure of patients. 8 Exercise results in modification of blood flow, luminal shear stress, arterial pressure, and tangential wall stress, all of which are factors that can induce changes in arterial function, diameter, and wall thickness.…”
Section: Discussionsupporting
confidence: 93%
“…women). 6 We compared the changes in blood pressure in the intervention group with that in the control group. Only a few patients experienced transient hypertension during the postural changes (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening by title and abstract, 18 records were eligible for full-text assessment. Five studies remained available for qualitative synthesis after assessment of the eligibility criteria 23–27. The study by Zhou et al27 was identified by forward citation searching (ie, identified through other sources).…”
Section: Resultsmentioning
confidence: 99%
“…Ten patients participated in exercise-based CR and completed the exercise test, three of whom had Marfan syndrome. Tabet et al26 included data from 54 patients with surgically treated aortic root aneurysm or ascending aorta aneurysm with a mean age of 50 ± 13 yr. Zhou et al27 included data from 75 patients with surgically treated type A aortic dissection with a mean age of 62 ± 13 yr.…”
Section: Resultsmentioning
confidence: 99%